Mechanically Stacked Triple-junction GaInP / GaAs / Si Solar Cell Simulation - A.B. Gnilenko; S.V. Plaksin (Журнал нано- та електронної фізики)
Mechanically stacked triple-junction GaInP / GaAs / Si solar cell is simulated by Silvaco TCAD computer software and compared to more conventional GaInP / GaAs / Ge mechanically stacked configuration. External quantum efficiency, I-V characteristics and basic I-V parameters are obtained to demonstrate the advantages of using the silicon active substrate as the bottom sub-cell instead of the germanium substrate based bottom sub-cell.